Genetics, genomics and breeding of soybean - Bilyeu, Kristin D.; Kole, Chittaranjan; Ratnaparkhe, Milind B. (Genetics, genomics and breeding of crop plants, 2010)
In addition to human consumption, the soybean is a major protein source in animal feeds and is becoming a major crop for biodiesel production. Bridging traditional research with modern molecular investigations on soybean, this volume explores the advances in soybean genome mapping, molecular breeding, genomics, sequencing, and bioinformatics